2018
DOI: 10.12809/hkmj176875
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy: its use in medical emergencies and its development in Hong Kong

Abstract: Hyperbaric oxygen therapy is widely accepted as life-saving treatment for decompression illness. Yet its use in acute carbon monoxide poisoning has remained controversial because of inconsistent findings in clinical trials. Hyperbaric oxygen therapy has an adjunctive role in managing gas gangrene, necrotising soft-tissue infection, and crush injury, as supported by case series. Several cases have been reported in the literature detailing the use of hyperbaric oxygen therapy in patients with severe anaemia in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…The results of present study support that HO 2 treatment procedures can be developed for people with AD. However, HO 2 treatment at certain conditions cloud produce some complications such as middle ear, lung, or sinus barotrauma when hyperbaric pressure is used, and neurological, retinal, and pulmonary oxygen toxicity caused by high oxygen level (Grim, Gottlieb, Boddie, & Batson, ; Leung & Lam, ). Pulmonary toxicity occurs when exposed to HO 2 at over 2.5 ATA for 6 hr or 1.5 ATA for over 12 hr at one session (Clark et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of present study support that HO 2 treatment procedures can be developed for people with AD. However, HO 2 treatment at certain conditions cloud produce some complications such as middle ear, lung, or sinus barotrauma when hyperbaric pressure is used, and neurological, retinal, and pulmonary oxygen toxicity caused by high oxygen level (Grim, Gottlieb, Boddie, & Batson, ; Leung & Lam, ). Pulmonary toxicity occurs when exposed to HO 2 at over 2.5 ATA for 6 hr or 1.5 ATA for over 12 hr at one session (Clark et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bowel compression determines hypoxia and the secondary hyperechoic aspect. When possible, a paracentesis should be performed for decompression of the abdominal viscera and diagnostic tests, allowing the intestines and the diaphragm to resume a normal position and development [78]. To improve the fetal outcome, we performed a fetal paracentesis with complete resolution of the ascites in 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…El Bishry et al monitored 12 cases of isolated fetal ascites and reported complete resolution of fetal ascites after paracentesis in 50% of the cases (30% antepartum and 20% after birth). Reducing the diaphragm compression on the lungs by paracentesis allows for proper pulmonary development and function after birth [78]. A paracentesis may be repeated in cases when the asIites level increases again.…”
Section: Discussionmentioning
confidence: 99%
“…These are the cases of some infections above mentioned, decompression sickness, air or gas embolism, acute arterial insufficiencies such as central retinal arterial occlusion (CRAO), crush injury, compartment syndrome and acute traumatic ischemia, along with CO/Cyanide poisoning [89]. In this context, the central role of HBOT is derived from the rapid and effective response of the tissues under certain conditions that may be severe and even life-threatening [90].…”
Section: Hbot In Medical Emergenciesmentioning
confidence: 99%